UK and Irish Y-STR population data—A catalogue of variant alleles. (May 2018) - Aliferi, Anastasia; Thomson, Jim; McDonald, Andrew; Paynter, Vanessa Molin; Ferguson, Steven; Vanhinsbergh, Des; Syndercombe Court, Denise; Ballard, David
Highlights: Reporting 3128 Powerplex Y23 profiles from four UK and Irish populations. Investigation into shared haplotypes using 5 additional loci included in Yfiler Plus kit. Investigation into allele duplications and deletions. Sequencing of primer binding and mobility shift mutations in loci DYS481, DYS392 and DYS576. Abstract: A total of 3128 Y-STR profiles from three UK and one Irish population have been analysed with the PowerPlex Y23 system and are reported here. Instances of haplotype sharing between apparently unrelated individuals were identified and further investigated with the use of the 5 additional markers within the Yfiler Plus kit, resulting in a reduction by 76% in the number of shared haplotypes. Furthermore, Yfiler Plus was also employed to verify locus deletions and duplications observed in Y23 genotypes while inconsistencies between the two kits were sequenced, revealing underlying Y23 primer binding site mutations in loci DYS392 and DYS576. Finally, the mechanism behind a previously reported population specific peak shift observed in DYS481 in South Asian samples has been evaluated and further investigated in a novel case of this phenomenon seen in a Black British individual featuring a different flanking region mutation.